Environment-friendly degradable packing belt for bundling and packaging and preparation method of environment-friendly degradable packing belt

By combining a polylactic acid base layer and a hemp rope mesh layer, the problem of insufficient mechanical properties of biodegradable packing straps is solved, and packing straps with high strength, environmental protection and biodegradability are prepared, which meet the requirements of high strength and extend service life.

CN120921758APending Publication Date: 2025-11-11HAINING YUEHAI COLOR PRINTING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510986323.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-17
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Biodegradable packing tape has poor mechanical properties and cannot meet certain high-strength requirements, affecting its application range and lifespan.

Method used

The packing strap adopts a combination structure of polylactic acid base layer and hemp rope mesh layer. The polylactic acid base layer is composed of polylactic acid resin, bamboo fiber, triethyl citrate, waste pulp and zinc oxide, while the hemp rope mesh layer is composed of hemp rope fiber and modified starch. The packing strap is prepared by hot pressing to enhance its mechanical strength and environmental performance.

Benefits of technology

It improves the overall strength and deformation resistance of the strapping, ensuring that it is not easily broken during the binding process. It also has good environmental performance and can be naturally degraded, reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005504519200000101
    Figure BDA0005504519200000101
Patent Text Reader

Abstract

The invention belongs to the technical field of packing belt materials, and particularly discloses an environment-friendly degradable packing belt for bundling and packaging and a preparation method of the environment-friendly degradable packing belt. The environment-friendly degradable packing belt for bundling and packaging comprises a polylactic acid base layer, a hemp rope grid layer and a polylactic acid base layer, and the polylactic acid base layer is prepared from polylactic acid resin, bamboo fibers, triethyl citrate, waste paper pulp, zinc oxide and rosin resin; the hemp rope grid layer comprises the following raw materials: hemp rope fibers and modified starch. According to the packaging belt, all the raw materials and all the layer structures are mixed, so that the mechanical performance of the packaging belt is remarkably improved, the packaging belt has good strength and toughness, and the durability of the packaging belt is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of packing strap materials, and in particular to an environmentally friendly, biodegradable packing strap and its preparation method. Background Technology

[0002] Strapping, a commonly used packaging material, serves to secure goods, preventing them from scattering or shifting during transportation and storage, thus ensuring their integrity and safety. Types of strapping typically include polypropylene strapping, steel strapping, nylon strapping, fiber strapping, and biodegradable strapping. With increasing environmental awareness, the demand for biodegradable and recyclable strapping is growing to reduce the environmental pollution caused by traditional plastic strapping.

[0003] Biodegradable packing tape is an environmentally friendly type of packing tape. The raw materials typically include polylactic acid, cellulose, straw fiber, flame retardants, plasticizers, and fillers. The biodegradable packing tape is biodegradable, and the final degradation products are carbon dioxide, water, and small molecule biomass, which are harmless to the environment. It is widely used in the packaging of various products such as food, agricultural products, and daily necessities.

[0004] However, compared with traditional plastic strapping, biodegradable strapping has relatively poor mechanical properties (such as tensile strength), and may not meet the high strength requirements in some applications, thus affecting its scope of use and service life. Summary of the Invention

[0005] To improve the poor mechanical properties of biodegradable packing straps, this application provides an environmentally friendly biodegradable strapping strap and its preparation method.

[0006] This application provides an environmentally friendly, biodegradable strapping band for bundling and packaging, employing the following technical solution: An environmentally friendly and biodegradable strapping for bundling and packaging includes a polylactic acid (PLA) base layer, a hemp rope mesh layer, and a PLA base layer. The PLA base layer comprises the following raw materials: polylactic acid resin, bamboo fiber, triethyl citrate, waste paper pulp, zinc oxide, and rosin resin. The hemp rope mesh layer comprises the following raw materials: hemp rope fiber and modified starch.

[0007] By adopting the above technical solutions, the polylactic acid (PLA) base layer possesses certain mechanical strength and flexibility, capable of withstanding the tension and pressure during packaging, ensuring that the packing strap will not easily break during use. The hemp rope mesh layer has high strength and rigidity, and the woven mesh structure acts as a skeleton in the packing strap. The PLA base layer, hemp rope mesh layer, and PLA base layer work together to increase the overall strength and deformation resistance of the packing strap, preventing excessive local stretching or deformation during the bundling process.

[0008] In the polylactic acid (PLA) base layer, PLA resin possesses excellent biodegradability and mechanical properties, providing basic strength and toughness for the packing strap. Bamboo fiber increases the strength and rigidity of the packing strap, and as a renewable resource, its combination with PLA resin helps improve the environmental and mechanical properties of the packing strap. Triethyl citrate improves the flexibility and processing performance of PLA resin, making the packing strap easier to shape and use. Waste paper pulp has good adhesion and toughness, ensuring tight bonding between components and improving the strength and toughness of the packing strap. Zinc oxide, to some extent, regulates the degradation rate of PLA and also contributes to the antibacterial properties of the packing strap. Rosin resin has good adhesion and water resistance; combined with waste paper pulp and bamboo fiber, it can improve the cohesion and surface properties of the PLA base layer, making the packing strap more durable.

[0009] In the hemp rope mesh layer, the hemp rope fibers possess high strength and abrasion resistance. The mesh structure of the hemp rope fibers enhances the overall structural stability of the packing strap, preventing localized breakage during use. Modified starch, with its excellent adhesion and biodegradability, adheres to the surface of the hemp rope fibers, improving their structural strength and forming a stable mesh structure. It also increases the biodegradability of the hemp rope mesh layer. The combined use of the polylactic acid (PLA) base layer, the hemp rope mesh layer, and the appropriate combination of raw materials not only meets the performance requirements of the packing strap and improves its mechanical strength but also provides excellent environmental performance, allowing it to naturally degrade after use and reducing environmental pollution.

[0010] Preferably, by weight, the polylactic acid base layer comprises: 60-70 parts polylactic acid resin, 15-20 parts bamboo fiber, 10-14 parts triethyl citrate, 35-40 parts waste pulp, 5-7 parts zinc oxide, and 3-6 parts rosin resin; the hemp rope mesh layer comprises: 30-40 parts hemp rope fiber and 15-18 parts modified starch.

[0011] By adopting the above technical solution and further limiting the amount of raw materials used in each component, the resulting polylactic acid base layer has good mechanical properties, environmental friendliness, and biodegradability; the resulting hemp rope mesh layer has good toughness and structural strength; and the combination of each layer results in a packing strap with good mechanical properties and biodegradability, extending the durability of the packing strap.

[0012] Preferably, the method for preparing the waste pulp includes the following steps: (1) Shred waste newspapers and corrugated paper, disperse them in sodium hydroxide solution, stir for 2-3 hours, filter, disperse in deionized water, add glyoxal, stir for 1-2 hours to obtain mixture A; (2) Grind the slag powder, sieve it, then disperse it in deionized water, add sodium thiosulfate and gypsum, stir for 20-25 minutes, dry it, and obtain mixture B; (3) Add mixture B from step (2) to mixture A from step (1), stir for 40-45 min, then add acetic acid solution of chitosan, stir for 2-3 h, dry, grind, and obtain waste pulp.

[0013] By employing the above technical solution, sodium hydroxide solution dissolves some impurities such as lignin in the paper, enabling the initial separation and purification of waste newspapers and corrugated paper. Simultaneously, it reacts with some functional groups on the surface of the waste newspapers and corrugated paper, increasing their activity. Glyoxal can undergo cross-linking reactions with hydroxyl groups and other functional groups in the waste newspapers and corrugated paper, thereby improving the strength and stability of mixture A and facilitating its subsequent compounding with other components.

[0014] Slag powder has good strength, durability, and thermal stability. Sodium thiosulfate modifies the surface of slag powder, making it easier to combine with other substances. Gypsum and slag powder undergo a hydration reaction in water to generate some substances with cementing properties, giving mixture B a certain degree of adhesion and strength, which helps in subsequent mixing with other components.

[0015] Mixtures A and B are combined, allowing treated waste newspapers, corrugated paper, slag powder, and gypsum to fully contact and interact, binding together through physical adsorption and chemical bonding to form a composite system, thus improving the overall performance of the mixture. Adding a chitosan acetic acid solution, which exhibits good biocompatibility, biodegradability, film-forming properties, and antibacterial activity, further enhances the system's stability and adhesion by allowing chitosan molecules to interact with the functional groups on the surfaces of the waste newspapers, corrugated paper, and slag powder. This also imparts strength and toughness to the waste pulp. When subsequently applied to polylactic acid (PLA) base layers, in conjunction with other components, it improves the mechanical strength, adhesion, and durability of the PLA base layer.

[0016] Preferably, the mass ratio of the waste newspaper, slag powder and chitosan acetic acid solution is 1:0.6-0.8:0.3-0.4.

[0017] By adopting the above technical solution and further limiting the mass ratio of waste newspaper, slag powder, and chitosan acetic acid solution within a certain range, the resulting waste pulp exhibits excellent comprehensive properties. After treatment, the waste newspaper possesses certain toughness, adhesion, and tensile strength, while the slag powder has a certain rigidity. After grinding, it is uniformly dispersed in the system, filling the gaps in the waste newspaper to form a stable composite structure, providing reinforcement and improving overall hardness and compressive strength. Chitosan molecules, through their amino and hydroxyl functional groups, interact with the active groups on the surface of the waste newspaper fibers and slag powder via hydrogen bonding, electrostatic attraction, or chemical reactions, thereby bonding the fibers and slag powder more tightly together, further enhancing the structural stability of the composite system. When subsequently applied to packing straps, this improves the durability of the straps, enabling them to withstand greater pressure and tension, reducing breakage during strapping, and exhibiting good biodegradability.

[0018] Preferably, the method for preparing the acetic acid solution of chitosan includes the following steps: dispersing nano-silica in deionized water, adding a silane coupling agent, stirring for 15-20 minutes to obtain a mixed solution; Chitosan was dispersed in an acetic acid solution, and alumina fiber, water-based epoxy resin adhesive and mixture were added. The mixture was stirred at 65-70℃ for 1-2 hours to obtain an acetic acid solution of chitosan.

[0019] By employing the above technical solutions, nano-silica possesses a large specific surface area and surface activity, forming a good bond with chitosan molecules, thereby improving the tensile strength and modulus of the solution. Silane coupling agents can improve the compatibility between nano-silica and chitosan, enhancing their bonding force and thus improving the mechanical properties of the solution. Alumina fibers, with their high strength, high hardness, high temperature resistance, and high modulus, intertwine with chitosan molecules, enhancing the mechanical properties of the material and providing a good reinforcing effect, improving the tensile strength and abrasion resistance of the solution. Waterborne epoxy resin adhesives have excellent bonding properties, firmly binding chitosan, alumina fibers, and nano-silica together to form a stable network structure, thereby improving the overall cohesion and comprehensive performance of the material. When applied to waste pulp, it improves the adhesion between the components in the waste pulp, aids in the film-forming properties of the waste pulp, and subsequently improves the flexibility and mechanical strength of the packing straps.

[0020] Preferably, the method for preparing the modified starch includes the following steps: (1) Disperse starch, montmorillonite, EDTA and maleic anhydride in deionized water and mix at 80-90℃ for 30-35 min to obtain mixed powder; (2) Remove the seeds from the cotton, disperse it in citric acid solution, soak it for 10-14 minutes, wash it with water, then disperse it in deionized water, add the mixed powder from step (1), sonicate it for 2-3 hours, and dry it to obtain a mixture; (3) Spray sodium alginate solution onto the surface of the mixture in step (2) and dry to obtain modified starch.

[0021] By employing the above technical solutions, maleic anhydride forms chemical bonds with starch molecules, enhancing intermolecular forces and thus improving the mechanical properties and heat resistance of starch. The combination of starch and montmorillonite allows the nano-properties of montmorillonite to interact and intercalate with the starch-based materials, improving the system's thermal stability and mechanical strength. EDTA interacts with certain groups on starch molecules, altering the gelatinization and rheological properties of starch, making it easier for starch molecules to be compounded with other components, and enhancing the system's cross-linking density and stability.

[0022] After deseeding, cotton fibers are dispersed and soaked in a citric acid solution. Citric acid provides a mild acidification treatment to the cotton fibers, making the functional groups such as hydroxyl groups on the fiber surface more easily exposed and increasing the fiber's reactivity. A mixed powder is then uniformly dispersed around the cotton fibers, promoting interaction between the powder and the fibers. Substances such as starch and montmorillonite in the mixed powder are adsorbed onto the surface of the cotton fibers or undergo physical or chemical bonding, thereby improving the strength, heat resistance, and water resistance of the cotton fibers.

[0023] A sodium alginate solution is sprayed onto the surface of the mixture. The sodium alginate solution has good film-forming and adhesive properties. The sodium alginate will form a uniform film on the surface of the mixture. This film will wrap the mixed powder and cotton fibers, etc., and play a protective and adhesive role, preventing the loss and scattering of internal components. It will improve the mechanical properties, adhesiveness and film-forming properties of the modified starch. It will then be used in packing straps to improve the mechanical properties, water resistance, stability and degradability of the packing straps.

[0024] Preferably, the mass ratio of starch, cotton and sodium alginate solution is 1:0.4-0.5:0.2-0.3.

[0025] By adopting the above technical solution and further limiting the mass ratio of starch, cotton, and sodium alginate solution within a certain range, the resulting modified starch exhibits superior comprehensive performance. Starch itself possesses certain viscosity, flexibility, and biodegradability. When mixed with cotton, the cotton exhibits higher strength and toughness. The cotton fibers intertwine and bond with starch and other components, forming a structure similar to a fiber-reinforced composite material, improving the tensile strength and tear resistance of the system. Sodium alginate solution has certain film-forming properties, ensuring tight adhesion between starch and cotton, further enhancing bonding and reinforcement, and improving the binding force between the components. Subsequent application in packing straps results in a denser structure, improved stability and weather resistance, a more robust overall structure, and extended service life.

[0026] Preferably, the method for preparing the sodium alginate solution includes the following steps: dispersing sodium alginate in deionized water, adding gelatin, and obtaining a mixture; Graphene was dispersed in anhydrous ethanol, nanocrystalline cellulose was added, and the mixture was stirred at 60-65℃ for 30-36 minutes and then dried to obtain a mixture. Add the mixture to the mixed solution and stir at 70-75℃ for 2-3 hours to obtain sodium alginate solution.

[0027] By adopting the above technical solution, gelatin and sodium alginate interact to form a more stable network structure, which effectively enhances the tensile strength, viscosity and flexibility of the mixture, and can be used as a matrix material and binder in subsequent steps.

[0028] Graphene possesses excellent thermal stability and mechanical properties, which can significantly improve the thermal stability of the system, allowing it to maintain good performance even at high temperatures. Nanocrystalline cellulose, on the other hand, has high strength and modulus, which can improve the overall mechanical properties of the mixture. Graphene loaded into the nanocrystalline cellulose structure enhances the structural strength of the mixture.

[0029] The mixture is added to the liquid mixture and stirred until homogeneous. The graphene and nanocrystalline cellulose components are uniformly dispersed in the liquid mixture containing sodium alginate and gelatin. The network structure of sodium alginate and gelatin further cross-links, enhancing the bonding force between the reinforcing materials such as graphene and the matrix. This results in a sodium alginate solution with superior properties, such as higher strength, toughness, and stability. This solution is then applied to modified starch to improve its properties, ultimately enhancing the overall performance of the packing tape.

[0030] Preferably, the preparation method of the hemp rope mesh layer includes the following steps: weaving hemp rope fibers into a mesh cloth, dispersing modified starch in deionized water, immersing the obtained mesh cloth in it, soaking 2-3 times, and drying for 10-15 minutes each time to obtain the hemp rope mesh layer.

[0031] By adopting the above technical solution, hemp rope fibers possess a certain strength and flexibility. Using them as warp and weft threads to weave a mesh fabric provides a supporting framework for subsequent modified starch impregnation. This mesh fabric structure allows for better adhesion and penetration of the modified starch, and the inherent properties of the hemp rope fibers also endow the final product with certain mechanical properties.

[0032] Immersing the mesh fabric in a modified starch solution allows the modified starch to fully contact and adhere to the surface of the hemp rope fibers. This results in a more continuous and thicker coating or network structure between the hemp rope fibers, thus enhancing its performance. The resulting hemp rope mesh layer combines the mechanical properties of the hemp rope fibers with overall strength and toughness, leading to better performance when used as packing straps or for other applications.

[0033] Secondly, this application also provides a method for preparing an environmentally friendly, biodegradable strapping for bundling and packaging, comprising the following steps: Polylactic acid resin, bamboo fiber, triethyl citrate, waste paper pulp, zinc oxide, and rosin resin are mixed to obtain a premix. The premix is ​​melt-extruded to obtain a polylactic acid base layer. The polylactic acid (PLA) base layer, hemp rope mesh layer, and PLA base layer are stacked in sequence, hot-pressed at 160-165℃, and cut into strips to obtain environmentally friendly and biodegradable strapping for packaging.

[0034] By adopting the above technical solution and preparation method, the operation is simple and the process time is short, which improves the production efficiency of preparing environmentally friendly biodegradable strapping for packaging. The resulting environmentally friendly biodegradable strapping for packaging has good mechanical properties, biodegradability and durability.

[0035] In summary, this application has the following beneficial effects: 1. In this application, the polylactic acid base layer, the hemp rope mesh layer and the polylactic acid base layer work together to increase the overall strength and deformation resistance of the packing strap, and prevent the packing strap from being stretched or deformed excessively in a localized manner during the bundling process.

[0036] 2. The waste pulp in this application has good viscosity and toughness, which makes the components bond tightly, improves the strength and toughness of the packing strap, and the reasonable combination of raw materials meets the performance requirements of the packing strap.

[0037] 3. In this application, the polylactic acid base layer, hemp rope mesh layer and polylactic acid base layer are used in combination to improve the mechanical strength of the packing strap, which has good environmental performance and can be naturally degraded after use, reducing pollution to the environment. Detailed Implementation

[0038] The present application will be further described in detail below with reference to the embodiments.

[0039] The raw materials used in the examples and comparative examples are all commercially available.

[0040] Example of waste paper pulp preparation Preparation Example 1 The method for preparing waste paper pulp includes the following steps: (1) Crush 80kg of waste newspapers and 20kg of corrugated paper, disperse them in 160L of sodium hydroxide solution with a mass fraction of 6%, stir for 2.5h, filter, disperse in 360L of deionized water, add 10kg of glyoxal, stir for 1.6h, and obtain mixture A; (2) Grind the slag powder, pass it through a 45μm sieve, then disperse it in 90L of deionized water, add 15kg of sodium thiosulfate and 18kg of gypsum, stir for 23min, dry, and obtain mixture B; (3) Add mixture B from step (2) to mixture A from step (1), stir for 42 min, then add acetic acid solution of chitosan, stir for 3 h, dry, grind, and obtain waste pulp.

[0041] The mass ratio of waste newspaper, slag powder, and chitosan acetic acid solution is 1:0.6:0.4.

[0042] The preparation method of chitosan acetic acid solution includes the following steps: 15 kg of nano silica is dispersed in 20 L of deionized water, 1.5 kg of silane coupling agent KH550 is added, and the mixture is stirred for 18 min to obtain a mixed solution; 40 kg of chitosan was dispersed in 80 L of 8% acetic acid solution. 3 kg of alumina fiber, 6 kg of water-based epoxy resin adhesive, and the mixture were added. The mixture was stirred at 70°C for 2 hours to obtain a chitosan acetic acid solution. The water-based epoxy resin adhesive was purchased from Shandong Kebang Chemical Co., Ltd.

[0043] Preparation Example 2 The difference from Preparation Example 1 is that no slag powder is added in step (2).

[0044] Preparation Example 3 The difference from Preparation Example 1 is that in step (3), the acetic acid solution of chitosan is not added.

[0045] Preparation Example 4 The difference from Preparation Example 1 is that the mass ratio of waste newspaper, slag powder and chitosan acetic acid solution is 1:0.8:0.3.

[0046] Preparation Example 5 The difference from Preparation Example 1 is that the mass ratio of waste newspaper, slag powder and chitosan acetic acid solution is 1:0.1:0.9.

[0047] Preparation Example 6 The difference from Preparation Example 1 is that nano-silica is not added in the preparation method of chitosan acetic acid solution.

[0048] Preparation Example 7 The difference from Preparation Example 1 is that the preparation method of the chitosan acetic acid solution does not involve the addition of an aqueous epoxy resin adhesive.

[0049] Example of preparation of modified starch Preparation Example 8 The method for preparing modified starch includes the following steps: (1) Disperse 26 kg of corn starch, 12 kg of montmorillonite, 3 kg of EDTA and 2 kg of maleic anhydride in 100 L of deionized water and mix at 85 °C for 32 min to obtain a mixed powder; (2) Remove the seeds from the cotton, disperse it in 50L of 10% citric acid solution, soak for 12min, wash with water, then disperse it in 150L of deionized water, add the mixed powder from step (1), sonicate for 2.5h, dry, and obtain the mixture. (3) Spray sodium alginate solution onto the surface of the mixture in step (2) and dry to obtain modified starch.

[0050] The mass ratio of starch, cotton, and sodium alginate solution is 1:0.4:0.3.

[0051] The method for preparing sodium alginate solution includes the following steps: dispersing 15 kg of sodium alginate in 100 L of deionized water, adding 5 kg of gelatin to obtain a mixed solution; 7 kg of graphene was dispersed in 80 L of anhydrous ethanol, 8 kg of nanocrystalline cellulose was added, the mixture was stirred at 62 °C for 35 min, and then dried to obtain a mixture. The mixture was added to the liquid mixture and stirred at 72℃ for 2.5 hours to obtain a sodium alginate solution. The nanocrystalline cellulose was purchased from Hebei Pengyu Biotechnology Co., Ltd. Preparation Example 9 The difference from Preparation Example 8 is that cotton is not added in step (2).

[0052] Preparation Example 10 The difference from Preparation Example 8 is that sodium alginate solution is not added in step (3).

[0053] Preparation Example 11 The difference from Preparation Example 8 is that the mass ratio of starch, cotton and sodium alginate solution is 1:0.5:0.2.

[0054] Preparation Example 12 The difference from Preparation Example 8 is that the mass ratio of starch, cotton and sodium alginate solution is 1:0.05:0.5.

[0055] Preparation Example 13 The difference from Preparation Example 8 is that graphene is not added in the preparation method of sodium alginate solution.

[0056] Preparation Example 14 The difference from Preparation Example 8 is that nanocrystalline cellulose is not added in the preparation method of sodium alginate solution. Example

[0057] Example 1 An environmentally friendly and biodegradable strapping for bundling and packaging includes a polylactic acid base layer, a hemp rope mesh layer, and a polylactic acid base layer. By weight, the polylactic acid base layer includes: 70 kg of polylactic acid resin, 20 kg of bamboo fiber, 14 kg of triethyl citrate, 40 kg of waste paper pulp, 5 kg of zinc oxide, and 3 kg of rosin resin. The hemp rope mesh layer consists of 40 kg of hemp rope fiber and 18 kg of modified starch.

[0058] The method for preparing a hemp rope mesh layer includes the following steps: weaving hemp rope fibers into a mesh fabric, with the hemp rope fibers serving as both warp and weft threads, resulting in a mesh fabric with an areal density of 100 g / m². 2 The thickness of the mesh fabric is 0.07mm; Modified starch was dispersed in 46L of deionized water, and the resulting mesh fabric was immersed in it. The immersion was repeated 3 times, and each time it was dried for 15 minutes to obtain a hemp rope mesh layer.

[0059] The twist of the hemp rope fiber is 1000T / M.

[0060] The above-mentioned method for preparing environmentally friendly and biodegradable strapping for packaging includes the following steps: mixing polylactic acid resin, bamboo fiber, triethyl citrate, waste pulp, zinc oxide, and rosin resin to obtain a premix; and melting and extruding the premix to obtain a polylactic acid base layer. The polylactic acid base layer, hemp rope mesh layer and polylactic acid base layer are stacked in sequence, hot-pressed at 162℃ for 5 minutes, and then cut into strips to obtain environmentally friendly and biodegradable strapping for packaging.

[0061] The mixing temperature is 150℃, and the extrusion temperature is 170℃.

[0062] Waste pulp was prepared using Preparation Example 1, and modified starch was prepared using Preparation Example 8.

[0063] Example 2 An environmentally friendly and biodegradable strapping for bundling and packaging differs from Example 1 in that, by weight, the polylactic acid base layer comprises: 60 kg of polylactic acid resin, 15 kg of bamboo fiber, 10 kg of triethyl citrate, 35 kg of waste pulp, 7 kg of zinc oxide, and 6 kg of rosin resin. The hemp rope mesh layer consists of 30 kg of hemp rope fiber and 15 kg of modified starch.

[0064] Example 3 An environmentally friendly, biodegradable strapping for bundling packaging differs from Example 1 in that the waste pulp is prepared using Preparation Example 2.

[0065] Example 4 An environmentally friendly, biodegradable strapping for bundling packaging differs from Example 1 in that the waste pulp used is prepared using Preparation Example 3.

[0066] Example 5 An environmentally friendly, biodegradable strapping for bundling packaging differs from Example 1 in that the waste pulp is prepared using Preparation Example 4.

[0067] Example 6 An environmentally friendly, biodegradable strapping for bundling packaging differs from Example 1 in that the waste pulp is prepared using Preparation Example 5.

[0068] Example 7 An environmentally friendly, biodegradable strapping for bundling packaging differs from Example 1 in that the waste pulp is prepared using Preparation Example 6.

[0069] Example 8 An environmentally friendly, biodegradable strapping for bundling packaging differs from Example 1 in that the waste pulp is prepared using Preparation Example 7.

[0070] Example 9 An environmentally friendly, biodegradable strapping for bundling packaging differs from Example 1 in that the modified starch is prepared using Preparation Example 9.

[0071] Example 10 An environmentally friendly, biodegradable strapping for bundling packaging differs from Example 1 in that the modified starch is prepared using Preparation Example 10.

[0072] Example 11 An environmentally friendly, biodegradable strapping for bundling packaging differs from Example 1 in that the modified starch is prepared using Preparation Example 11.

[0073] Example 12 An environmentally friendly, biodegradable strapping for bundling packaging differs from Example 1 in that the modified starch is prepared using Preparation Example 12.

[0074] Example 13 An environmentally friendly, biodegradable strapping for bundling packaging differs from Example 1 in that the modified starch is prepared using Preparation Example 13.

[0075] Example 14 An environmentally friendly, biodegradable strapping for bundling packaging differs from Example 1 in that the modified starch is prepared using Preparation Example 14.

[0076] Comparative Example Comparative Example 1 An environmentally friendly, biodegradable strapping for bundling packaging differs from Example 1 in that it does not contain waste paper pulp.

[0077] Comparative Example 2 An environmentally friendly, biodegradable strapping for bundling packaging differs from Example 1 in that it does not contain modified starch.

[0078] Performance testing The environmentally friendly biodegradable strapping tapes prepared in Examples 1-14 and Comparative Examples 1-2 were subjected to performance tests; the tensile test was conducted in accordance with the standard GB / T1040-2006, and the tensile strength and elongation at break were tested.

[0079] The bending strength was tested according to GB / T 9341-2008, and the notched impact strength was tested according to GB / T 1043.1-2008. The test results are shown in Table 1.

[0080] Table 1 Test data for the examples and comparative examples As shown in Table 1, the environmentally friendly biodegradable strapping tapes prepared in Examples 1-2 of this application have good mechanical properties and flexural strength. Among them, Example 1 has a tensile strength of 59.8 MPa, an elongation at break of 21.6%, a flexural strength of 78.6 MPa, and a notched impact strength of 10.32 KJ / m. 2 It is evident that the material prepared in this application possesses good strength and toughness, and the interaction between the components and layers improves the mechanical properties of the environmentally friendly and biodegradable strapping, resulting in good durability.

[0081] The degradation rate refers to the degradation rate of the packing tape prepared in Example 1 after 6 months of degradation according to the ASTM D5272-92 outdoor exposure test standard for photodegradable plastics. This indicates that the packing tape prepared in this application has good environmental protection properties.

[0082] In Examples 3-4, the preparation methods of waste paper pulp did not include slag powder or chitosan acetic acid solution. In Examples 5-6, the mass ratio of waste newspaper, slag powder, and chitosan acetic acid solution was changed. Table 1 shows that the tensile strength, elongation at break, flexural strength, and notched impact strength of Examples 3-4 were significantly worse than those of Examples 1-2 and Example 5. The corresponding performance of Example 6 was better than that of Examples 3-4, but worse than that of Examples 1-2 and Example 5. This indicates that slag powder fills the gaps in the waste newspaper, forming a stable composite structure that acts as a reinforcement. Chitosan molecules interact with the waste newspaper fibers and the active groups on the surface of the slag powder through their amino and hydroxyl functional groups, bonding the fibers and slag powder more tightly together, further enhancing the structural stability of the composite system. When subsequently applied to packing straps, this makes the straps less prone to breakage when bundling items.

[0083] In Examples 7-8, the preparation methods of chitosan acetic acid solutions did not include nano-silica or waterborne epoxy resin adhesive. Table 1 shows that the tensile strength, elongation at break, flexural strength, and notched impact strength of Examples 7-8 were significantly worse than those of Examples 1-2, but better than Example 4. This indicates that the waterborne epoxy resin adhesive firmly bonds chitosan, alumina fibers, and nano-silica together to form a stable network structure, thereby improving the overall cohesion and comprehensive performance of the material. When applied to waste pulp, it enhances the adhesion between components in the waste pulp and improves the flexibility and mechanical strength of the packing straps.

[0084] In Examples 9-10, the modified starch preparation methods did not include cotton or sodium alginate solution, while Examples 11-12 varied the mass ratio of starch, cotton, and sodium alginate solution. Table 1 shows that the tensile strength, elongation at break, flexural strength, and notched impact strength of Examples 9-10 were significantly worse than those of Examples 1-2 and Example 11. In Example 12, the corresponding performance was better than that of Examples 9-10, but worse than that of Examples 1-2 and Example 11. This indicates that the sodium alginate solution makes the starch and cotton adhere more tightly, further strengthening and reinforcing the structure, and improving the bonding force between the components. Subsequent application in packing straps improves the stability and weather resistance of the straps, making the overall structure more robust and extending their service life.

[0085] In Examples 13-14, the preparation methods of sodium alginate solutions did not include graphene or nanocrystalline cellulose. As shown in Table 1, the tensile strength, elongation at break, flexural strength, and notched impact strength of Examples 13-14 were significantly worse than those of Examples 1-2, but better than those of Example 10. This indicates that graphene loaded into the nanocrystalline cellulose structure improves the structural strength of the mixture. Subsequent application in modified starch enhances the corresponding properties of the modified starch, ultimately improving the overall performance of the packing tape.

[0086] Comparative Examples 1 and 2 were prepared without waste pulp and modified starch, respectively. Table 1 shows that the tensile strength, elongation at break, flexural strength, and notched impact strength of Comparative Examples 1 and 2 were significantly worse than those of Examples 1-2. This indicates that waste pulp has good adhesion and toughness, resulting in tight bonding between the components and improving the strength and toughness of the packing strap. Modified starch has good adhesion and biodegradability, adhering to the surface of the hemp rope fibers, improving the structural strength of the hemp rope fibers, forming a stable mesh structure, and also increasing the biodegradability of the hemp rope mesh layer.

[0087] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. An environmentally friendly, biodegradable strapping band for bundling and packaging, characterized in that, It includes a polylactic acid (PLA) base layer, a hemp rope mesh layer, and a PLA base layer. The PLA base layer comprises the following raw materials: polylactic acid resin, bamboo fiber, triethyl citrate, waste paper pulp, zinc oxide, and rosin resin. The hemp rope mesh layer comprises the following raw materials: hemp rope fiber and modified starch.

2. The environmentally friendly biodegradable strapping for bundling and packaging according to claim 1, characterized in that, The polylactic acid base layer, by weight, comprises: 60-70 parts polylactic acid resin, 15-20 parts bamboo fiber, 10-14 parts triethyl citrate, 35-40 parts waste pulp, 5-7 parts zinc oxide, and 3-6 parts rosin resin. The hemp rope mesh layer comprises: 30-40 parts of hemp rope fiber and 15-18 parts of modified starch.

3. The environmentally friendly biodegradable strapping for bundling and packaging according to claim 1, characterized in that, The method for preparing the waste pulp includes the following steps: (1) Shred waste newspapers and corrugated paper, disperse them in sodium hydroxide solution, stir for 2-3 hours, filter, disperse in deionized water, add glyoxal, stir for 1-2 hours to obtain mixture A; (2) Grind the slag powder, sieve it, then disperse it in deionized water, add sodium thiosulfate and gypsum, stir for 20-25 minutes, dry it, and obtain mixture B; (3) Add mixture B from step (2) to mixture A from step (1), stir for 40-45 min, then add acetic acid solution of chitosan, stir for 2-3 h, dry, grind, and obtain waste pulp.

4. The environmentally friendly biodegradable strapping for bundling and packaging according to claim 3, characterized in that, The mass ratio of the waste newspaper, slag powder, and chitosan acetic acid solution is 1:0.6-0.8:0.3-0.

4.

5. The environmentally friendly biodegradable strapping for bundling and packaging according to claim 3, characterized in that, The method for preparing the acetic acid solution of chitosan includes the following steps: dispersing nano-silica in deionized water, adding a silane coupling agent, stirring for 15-20 minutes to obtain a mixed solution; Chitosan was dispersed in an acetic acid solution, and alumina fiber, water-based epoxy resin adhesive and mixture were added. The mixture was stirred at 65-70℃ for 1-2 hours to obtain an acetic acid solution of chitosan.

6. The environmentally friendly biodegradable strapping for bundling and packaging according to claim 1, characterized in that, The method for preparing the modified starch includes the following steps: (1) Disperse starch, montmorillonite, EDTA and maleic anhydride in deionized water and mix at 80-90℃ for 30-35 min to obtain mixed powder; (2) Remove the seeds from the cotton, disperse it in citric acid solution, soak it for 10-14 minutes, wash it with water, then disperse it in deionized water, add the mixed powder from step (1), sonicate for 2-3 hours, dry it, and obtain the mixture. (3) Spray sodium alginate solution onto the surface of the mixture in step (2) and dry to obtain modified starch.

7. The environmentally friendly biodegradable strapping for bundling and packaging according to claim 6, characterized in that, The mass ratio of starch, cotton and sodium alginate solution is 1:0.4-0.5:0.2-0.

3.

8. The environmentally friendly biodegradable strapping for bundling and packaging according to claim 6, characterized in that, The method for preparing the sodium alginate solution includes the following steps: dispersing sodium alginate in deionized water, adding gelatin, and obtaining a mixture; Graphene was dispersed in anhydrous ethanol, nanocrystalline cellulose was added, and the mixture was stirred at 60-65℃ for 30-36 minutes and then dried to obtain a mixture. Add the mixture to the mixed solution and stir at 70-75℃ for 2-3 hours to obtain sodium alginate solution.

9. The environmentally friendly biodegradable strapping for bundling and packaging according to claim 1, characterized in that, The preparation method of the hemp rope mesh layer includes the following steps: weaving hemp rope fibers into a mesh cloth, dispersing modified starch in deionized water, immersing the obtained mesh cloth in it, soaking 2-3 times, and drying for 10-15 minutes each time to obtain the hemp rope mesh layer.

10. The method for preparing an environmentally friendly biodegradable strapping for bundling and packaging according to claim 1, characterized in that, Includes the following steps: Polylactic acid resin, bamboo fiber, triethyl citrate, waste paper pulp, zinc oxide, and rosin resin are mixed to obtain a premix. The premix is ​​melt-extruded to obtain a polylactic acid base layer. The polylactic acid (PLA) base layer, hemp rope mesh layer, and PLA base layer are stacked in sequence, hot-pressed at 160-165℃, and cut into strips to obtain environmentally friendly and biodegradable strapping for packaging.